Perceptions of Survivorship Care among Latina Women with Breast Cancer in Los Angeles County. Issue 2 (2nd November 2016) - Tisnado, Diana M.; Mendez‐Luck, Carolyn; Metz, Jenifer; Peirce, Katelynn; Montaño, Brian
Abstract: Objectives: Cancer "survivorship" is a distinct and important aspect of the cancer experience. More research is needed about survivorship care in underserved populations such as Latinas. This study examined issues of breast cancer survivorship care among Latinas to understand their experiences and needs, to inform the design of future programs. Design and Sample: Six English‐ and six Spanish‐language focus groups were conducted, with a nonprobability sample. About 74 Latinas who varied in terms of characteristics including stage, time since diagnosis, and English proficiency were recruited through support groups, health fairs, and promotoras . Measures: A semi‐structured question guide was used to examine experiences with follow‐up care, barriers, and meaning associated with breast cancer survivorship. Results: Results indicate numerous gaps and unmet needs in Latinas' survivorship care experiences, including problems with finances, continuity of care, unmet needs for information, and symptom management. Participants identified sources of support including patient navigators, and assigned both positive and negative meanings to survivorship. Conclusions: This research lays a foundation for future work to develop interventions addressing Latina breast cancer survivors' unmet needs. Recommendations include enhancing peer and professional support services for patients, family, and caregivers. Further work is also needed to promote the implementation of survivorship care plans.